THE ROLE OF FINANCIAL MANAGEMENT IN LONG-TERM INVESTMENT DECISION MAKING (LITERATURE REVIEW) - Daniyal, Dasrul; Tukiran, Martinus (International Journal of Multidisciplinary Research and Literature, 2024)
This study aims to examine the role of financial management in long-term investment decision-making through a literature review of various related studies. The main focus of this study is the impact of risk, the application of the time value of money, investment diversification, agency problems, and investment project feasibility evaluation techniques such as Net Present Value (NPV) and Internal Rate of Return (IRR). The literature review findings demonstrate that high risk influences investment decisions owing to the unpredictability of future cash flows, necessitating risk mitigation strategies like portfolio diversification and the utilization of derivative instruments. Applying the concept of the time value of money (TVM) is crucial in investment evaluation to facilitate more rational and profitable decisions, considering inflation and discount rates. Diversification of investments has demonstrated efficacy in mitigating volatility and enhancing long-term investment outcomes. Agency problems, which arise from conflicts of interest between owners and managers, also affect the quality of investment decisions, which can be overcome by designing incentives that align with the company’s long-term goals. Evaluating the feasibility of investment projects using NPV and IRR helps ensure that the investments can add significant value to the company. This research provides important insights into how good financial management can support more effective and sustainable investment decision-making